Correntional study of the health-related quality of life, chronic obstructive airway disease in Northern India, New Delhi - Ghilley, Ved Prakash; Bhadoria, D. P.; Pandit, Sanjay (International Journal of Advances in Medicine, 2018)
Background: The Global Initiative for Chronic Obstructive Lung Disease (GOLD) defines chronic obstructive pulmonary disease (COPD) as “a disease state characterized by airflow limitation that is not fully reversible. Due to progressive airflow limitation, the patients become increasingly symptomatic leading to worsening in their health-related quality of life (HRQOL). Objective of present study was to examine that correlation of health related quality of life with the chronic obstructive pulmonary disease. Methods: One hundred twenty consecutive stable COPD patients (diagnosed as per GOLD guidelines), without any co-morbid conditions (diabetes, congestive heart failure, coronary artery disease, hypertension) were recruited in this study after intuitional ethical clearance and informed consents. The health-related quality of life (HRQOL) was assessed using Hindi SGRQ-C. Forced expiratory volume in first one second (FEV1), forced vital capacity (FVC) and FEV1/FVC% and reversibility were measured using Spirolab III (Medical International Research USA, Inc.). The descriptive and the Pearson’s correlation coefficient were done in data treatment with SPSS version 20. Results: The component of SGRQ scores were as follows: Symptom score: 31.27±14.6 (range 2.3-64); Activity score: 59.01±23.08) (range 0-100); Impact score 42.19±22.25 (range 0-88.8) and the total score was = 45.34±17.96 (range 1.1.-88.6). There were significant negative correlations between all the parameters of SGRQ and FEV1% predicted (i.e. with lower FEV1% parameters of SGRQ will be high). Conclusions: Indian patients with COPD show significantly reduced HRQOL as measured by disease specific questionnaire SGRQ, similar to COPD patients in other countries. In our study, only FEV1 % predicted was significantly correlated with HRQOL, all other measures including GOLD staging were not significantly associated with HRQOL.